Media Interaktif Berbantuan Google Sites Untuk Penguatan Literasi dan Kemampuan Membaca Pemahaman Sekolah Dasar - Ahmad Zikri; Ardipal Ardipal; Muhammadi Muhamamdi; Jasrial Jasrial; Desyandri Desyandri (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Learning in reading literacy is not yet optimal, as it often focuses only on basic reading without deep comprehension and lacks effective use of digital technology, which becomes the main urgency of this study. This research aims to improve students’ reading comprehension skills through digital-based interactive learning using Google Sites. The study employed Classroom Action Research (CAR) conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects were a classroom teacher and 27 fifth-grade students of SDN 13 Batang Gasan, Kabupaten Padang Pariaman. Data were collected through lesson plan analysis, observations, interviews, and learning outcome tests, then analyzed using mixed methods. The results showed improvements in: (a) learning planning quality from 83.14% to 91.32%, (b) teacher activity from 80.73% to 88.59% and student activity from 78.93% to 87.59%, and (c) learning outcomes from 77.02 to 88.64. These findings indicate that digital-based literacy learning effectively enhances reading comprehension, increases student engagement, and creates a more active, interactive, and student-centered learning environment aligned with 21st-century education.